RELATIONSHIP BETWEEN FAMILY SUPPORT AND SELF MOTIVATION WITH COMPLIANCE IN TAKING MEDICATION IN PATIENTS WITH TUBERCULOSIS - Made Mahaguna Putra; Ni Made Dwi Yunica Astriani; Komang Gde Trisna Purwantara; Made Mernadi; Putu Indah Sintya Dewi (Journal of Nursing Science Update (JNSU), 2020)
Tuberculosis is one of the diseases that causes the biggest death in the world. TB is acontagious disease that can be cured but requires a long treatment. One of the factorsrelated to TB patient compliance in the treatment of one is family support and selfmotivation. The purpose of this study was to determine the relationship between familysupport and self-motivation with medication adherence for TB sufferers in the SawanI Community Health Center. This study was a correlation study with a cross-sectionaldesign. There are 53 respondents selected by nonprobability sampling with a purposivesampling technique. The data were analized with the Spearman rank test and theresult was significant relationship(p value 0.000) and coefficient correlation was 0,545which means it have positive relationship . It means there was a significant relationshipbetween family support and self-motivation to medication adherence for TB patients atthe Sawan I Community Health Center. In conclusion the better the family support andself-motivation of TB patients, the more obedient TB patients in treatment.